The Oxford handbook of gangs and society - Pyrooz, David C.; Densley, James A.; Leverso, John (Oxford University Press, 2024)
"The Oxford Handbook of Gangs and Society is the premier reference book on gangs for practitioners, policymakers, students, and scholars. This carefully curated volume contains 43 chapters written by the leading experts in the field, who advance a central theme of "looking back, moving forward" by providing state-of-the-art reviews of the literature they created, shaped, and (re)defined. This international, interdisciplinary collective of authors provides readers with a rare tour of the field in its entirety, expertly navigating thorny debates and the at-times contentious history of gang research, while simultaneously synthesizing flourishing areas of study that advance the field into the 21st century. The volume is divided into six cohesive sections that reflect the diverse field of gang studies and capture the large-scale cultural, economic, political, and social changes occurring within the world of gangs in the last century; anticipating immense changes on the horizon. From definitions to history to theory to epistemology to technology to policy and practice, this unprecedented volume captures the most timely and important topics in the field. When readers finish this book, they will be more confident in what we know and do not know about gangs in our society"--